PRINCIPAL MANAGEMENT TO IMPROVE THE QUALITY OF EDUCATORS AND EDUCATIONAL P ERSONNEL AT NURUL HUDA AL AZIZIYYAH HIGH SCHOOL - Tgk. Iskandarsyah Ismail (Media Inovasi Pendidikan dan Publikasi, 2024)
Education is an important instrument in human life. Education management is an integral component that cannot be separated from the overall educational process. The main pillars of education in schools are teachers and educational staff, therefore their quality and professionalism are the basis of hope in the world of education in order to provide good and dignified education. This research focuses on planning, organizing, moving and supervising school principal management to improve the quality of educators and education personnel at Nurul Huda Al 'Aziziyah High School Aceh Jaya. The aim of this research is to analyze the management of school principals to improve the quality of educators and education personnel. This type of research is qualitative with a case study approach. The design used is a single case design, namely a case study research that emphasizes research on only one case unit using purposive sampling techniques, observation methods, interviews and documentation. Data analysis was carried out by condensing data, presenting data and drawing conclusions through the process of selecting, narrowing, simplifying, summarizing and data transformation. The results of this research showed that in order to improve the quality of educators and educational staff at Nurul Huda Al Aziziyyah High School, the Principal has carried out his managerial duties as The principal goes through a process of planning, organizing, directing and supervising well in accordance with principal management standards.